Measuring the public’s perceptions of adult basic education - Richard A. Orem (Adult Education Research Conference, 1995)
This study was designed to measure public perception of the need for and quality of adult basic education in Illinois. Using a combination of data collection techniques, including focus groups and interviews with stakeholders, and a telephone survey of randomly selected Illinois residents, this study found a high level of support for continued public funding of adult basic education and a positive attitude toward adult basic education programs in general, but particularly among those with some knowledge of these programs.